2012
DOI: 10.1002/jcb.23402
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for metastatic melanoma

Abstract: Melanoma has traditionally been considered an immunogenic tumor. A number of approaches have been studied for enhancement of antitumor immunity. The first cytokine approved for the treatment of metastatic melanoma, interleukin-2, has resulted in prolonged responses in a small subset of patients, providing hope that immunotherapy might be useful for this disease. Ipilimumab, a monoclonal antibody to CTLA-4, was recently approved and a number of other promising investigational approaches are currently being purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Another strategy to treat melanoma that has received significant attention relies on immunotherapy 6 . Most recently, the blockade if immune checkpoints with the monoclonal antibody ipilimumab has been approved by the Food and Drug Administration (FDA) for the treatment of metastatic melanoma patients 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to treat melanoma that has received significant attention relies on immunotherapy 6 . Most recently, the blockade if immune checkpoints with the monoclonal antibody ipilimumab has been approved by the Food and Drug Administration (FDA) for the treatment of metastatic melanoma patients 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the blockade if immune checkpoints with the monoclonal antibody ipilimumab has been approved by the Food and Drug Administration (FDA) for the treatment of metastatic melanoma patients 7 . Other immunotherapeutic approaches being used or evaluated to treat melanoma include the use of cytokines including Type I interferons and interleukin (IL)-2, vaccines and adoptive T-cell transfer 6 , 8 . Various combinations of these strategies have also been evaluated and have shown encouraging results 9 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-2, the first cytokine permitted for use in patients with metastatic melanoma, has elicited sustained responses in a small subgroup of patients, providing hope that immunotherapy might be useful for this disease (3). Ipilimumab, a monoclonal antibody to CTLA-4, also has recently been approved by the FDA (37). The discovery of the BRAF mutation, following a genomewide analysis, revealed that 80% of BRAF mutations are V600E and this mutation is predominant in melanoma (5).…”
Section: Discussionmentioning
confidence: 99%
“…Additional immune-modulatory molecules that have gained scientific attention and are now under clinical development are OX40 (CD134), CD40, GITR, and 4-1BB (CD137) (http://www.clinicaltrials.gov/) (Table 1, also reviewed in [85]).…”
Section: Anti-melanoma Immunotherapiesmentioning
confidence: 99%